Multiple trichoepitheliomas. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2011)
Case report. A 7-year-old girl was first observed due to small lesions of the face started at the age of 2 years and slowly increased in number. The family history was negative for the presence of similar lesions. The physical examination (Fig. 1, 2) showed the presence on the cheeks, especially in the parotid region, of about fifty papules with a diameter between 0.5 and 2 mm. In some places the papules were very close to each other, without merging. The papules were pink, sometimes translucent, with a smooth surface. One papule was removed and its histological examination (Fig. 3, 4) showed aggregates of basaloid cells in the dermis not in contact with the epidermis and rare pilar structures. Immediately beneath the basement membrane of the basaloid cells, stromal cells showed palisading arrangement reminiscent of papillary mesenchymal bodies of the primary hair germ. The clinical and histological findings led to the final diagnosis of multiple trichoepitheliomas.